Effects of a rotating partition on mixed convection of hybrid nanofluid in a lid-driven cavity under different magnetic fields - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Aip Publishing, 2024)
There are many thermal engineering applications that employ partitions, such as heat exchangers, cryogenics, electronic cooling, and mixture separation. In this study, a novel type rotating partition is proposed and its performance is numerically assessed by the consideration of mixed convection in a lid-driven cavity with an inner isothermal blockage under magnetic field. A number of numerical simulations are run for various values of the Richardson number (0 <= Ri <= 50), rotational Reynolds number (0 <= Rew <= 50), Hartmann number of the inner domain (0 <= Ha <= 50), and non-dimensional size of the rotating partition (between 0.2 and 0.35). The experimental validation of the mixed convection for a lid-driven cavity is performed. It is observed the effects of rotation of the partition become important when natural convection effects become dominant. At the highest rotational speed, heat transfer reduction of 15% is obtained with increasing the Ri from 0.5 to 50, while at Ri = 50, partition rotation considering highest speed results in average Nusselt number (Nu) reduction by about 5.5%. Streamlines and isotherms are significantly affected by the size of the partition, while slight changes are obtained by varying the magnetic field strength. The reduction of Nu is obtained in the range of 8.5% and 8.8% with a higher magnetic field strength. The increments in the heat transfer by using the highest partition size are obtained in the range of 22.6% and 27.3%. When comparisons are made with non-partitioned lid-driven cavity, average Nu is reduced between 41.6% and 50% by using rotating partition. In the natural convection dominated case, heat transfer reduction will be 4% higher when rotations become active as compared to stationary partition. Feed forward recurrent network model with 25 neurons is used for accurate prediction of the thermal system of lid-driven cavity with rotating partition under magnetic field.
Keywords: Heat-Transfer; Natural-Convection; Entropy Generation; Square Cavity; Finite-Element; Flow; Enclosures; Channel; Radiation